Tillage Reduces Survival of Grape Berry Moth (Lepidoptera: Tortricidae), via Burial Rather Than Mechanical Injury. Issue 1 (8th February 2017) - Matlock, Jason M.; Isaacs, Rufus; Grieshop, Matthew
Abstract : The grape berry moth, Paralobesia viteana (Clemens), is a key pest of vineyards in eastern North America that overwinters as pupae in leaf litter on the vineyard floor. This presents an opportunity for tillage to disturb and bury the pupae, providing a potential nonchemical approach to control of this pest. Using a Lilleston-style rotary cultivator, we determined the distribution of pupae within the soil profile after single tillage passes, measured the type and severity of damage inflicted on pupae, and investigated how these effects on pupae influenced their survival. Survivorship of pupae recovered from the vineyard immediately after tillage and held until emergence was not significantly different from those recovered from an untilled control area, indicating little effect of mechanical damage on this pest. However, a single pass of the tillage implement buried three-quarters of pupae under at least 1 cm of soil. A laboratory experiment to recreate these conditions resulted in significant increase in mortality when pupae were buried in more than 1 cm of sand. We conclude that 1) interference with adult emergence of diapausing pupae via burial is the primary mechanism by which tillage controls grape berry moth, and 2) efforts to optimize the impact of tillage on grape berry moth populations should focus on maximizing the number of pupae buried. We discuss the potential integration of tillage into different vineyard management systems to enhance pest management.